Assessment of Effectiveness of Vinegar and Hydrogen Peroxide Based Herbicide Formulation Against Common Weeds in Thailand - Mahachai, Palisa; Subsoontorn, Pakpoom (Asian Health, Science and Technology Reports, 2021)
Acetic acid has been proposed by farmers and popular press as an environmentally friendly bioherbicide. Nonetheless, most relevant peer-reviewed studies were conducted in North America where weeds and environment may differ from other regions. Our greenhouse experiment in Thailand showed that vinegar (5% acetic acid) had weak herbicidal effects on crabgrass while 5% acetic acid + 5% salt + 0.2% dish soap killed crabgrass completely. In field trials, this formulation completely killed crabgrass, sleepy grass, Bermuda grass, torpedo grass and swamp morning glory after repeated applications. For organically compliant formulations, soapberry extract can be used in substitute for dish soap. To avoid soil salinization, salt content in the formulation can be reduced. 10% hydrogen peroxide + 0.2% dish soap eliminated most tested weed while 10% hydrogen peroxide + 0.2% soapberry extract suppressed sleepy grass but not other grassy weeds. These results provide the basis for developing bioherbicides for Thailand and other countries beyond North America.